PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN ADMINISTRASI DI UNIVERSITAS WIDYAGAMA MALANG - Budiantono, Bambang (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
The purpose of this study was to determine the effect of leadership and motivation simultaneously, to determine the effect of partial leadership and motivation, and to determine, which of the leadership and motivation are the dominant influence on employee performance. The research hypothesis is formulated as follows: 1. Leadership and motivation simultaneously significant effect on employee performance, leadership and motivation 2 partially significant effect on the performance of employees, and 3 Motivation is the dominant variable influence on employee performance. Leadership and motivation simultaneously significant effect on employee performance Widyagama University of Malang. 2 Leadership and motivation partially significant effect on employee performance Widyagama University, 3.Motivasi a dominant variable on employee performance Widyagama University of Malang Keywords: Leadership, Motivation and Performance